Building Relations with Generation Z as a Challenge for Social Customer Relationship Management Faced by Modern Enterprises - A Case of Generation Z Students - Anna Korombel; Olga Lawinska (International Journal of Supply Chain Management, 2019)
The Internet and access to numerous modern technological tools make it easier for modern enterprises to operate on the market, yet create ever more difficult conditions for being competitive. Competition is increasing very fast - it is currently at a mouse-click; the amount of time taken to make decisions is dramatically shrinking, enterprises' advertising and promotional campaigns are less and less effective, and the costs of attracting and retaining customers are rising. As customers' loyalty is decreasing and their awareness and expectations are increasing fast, it seems that the right solution for enterprises is to focus on building long-term relations with their customers. Such a possibility is offered by the concept of Social Customer Relationship Management (SCRM), which enables companies to develop two-way communication with customers through social media. In order to develop communication, enterprises need to find out as much as possible about their current/future interlocutor, i.e. their potential customer. There is extensive knowledge about the expectations and characteristics of social media activity of representatives of Silent Generation, the Baby Boomers, Generation X and Generation Y/Millennials. In contrast, Generation Z, i.e. people born in 1995 or later, who are currently entering the labour market, is the least explored generation. This group differs significantly from the representatives of the previous generations, which may be due to the fact that its representatives were born into the digital world and do not know other reality. The aim of the paper is to indicate the characteristics of social media activity of representatives of generation Z as a basis for building relations and gaining advantages by enterprises. This aim has been achieved by presenting part of the findings of a study conducted among students of the Management Faculty of the Czestochowa University of Technology in the third quarter of 2018.